Exploring infographic design in higher education context: towards a modular evaluation framework. Issue 1 (2nd January 2020) - Fragou, Olga; Papadopoulou, Maria
Abstract: Today's society is highly visual, imposing the use of respective practices in Higher Education; under this scope the importance of images and multimedia alters the way 21st digital literacy is perceived. As technology advances, it is important for education professionals to learn how to read visuals through practicing and analyzing techniques, but also support learners to use visuals as tools for effective communication in educational contexts. Recently, infographic activities have been introduced to the learning process as a new method of communication, supporting students in content generation. This paper aims to report on experience of using an addressed, modular evaluation framework for assessing twenty four (24) infographics produced by students in the context of the Module 'Design and Development of Educational Material and Digital Media' of the 'Language for Refugees and Migrants' (LRM) Post Graduate Programme hosted and run by the Hellenic Open University, the most prominent Greek educational institution in adult and distance learning. The combined application and conversion of two already available rubrics, led to the initial formation of a modular evaluation framework; identification and use of key concepts and specific criteria has taken place in the context of practically experiencing its implementation for evaluating Higher Education students' infographics. The data revealed important information regarding the students' visual literacy skills as reflected in their infographic artefacts in respect of content generation, information and data visualization.